P01.08 Beyond PD-1: characterization of new checkpoints restricting function of cytotoxic lymphocytes infiltrating human carcinoma. (1st October 2020) - Herbstritt, AS; Prinz, PU; Maxwell, M; Kadiyala, M; Yan, D; Noessner, E
Abstract : Background: T and NK cells from human renal cell carcinoma (RCC) are functionally non-responsive. Analysis of the TCR signaling cascade required for effector function identified that proximal signaling molecules were activated whereas activation of downstream ERK was blocked. Further investigation showed increased diacylglycerol kinase alpha (DGK-α) levels in T and NK cells from the RCC tumor microenvironment (TME). These cells were refractory to stimulation showing no degranulation or IFN-γ production. Using a small molecule DGK–α inhibitor (R59022), the function of tumor-infiltrating lymphocytes was restored ex vivo . A correlation of high DGK-α and loss of function was also observed in an experimental mouse model of adoptive therapy where CAR T cells that had lost their activity after infiltrating into solid tumors were found to have increased DGK-α. 1 Blockade of the Programmed cell death protein 1 (PD-1) with monoclonal antibodies is used in the clinic enabling some patients to achieve tumor control. However, not all patients respond. DGK-α activity is positioned downstream of PD-1 and should, if overactive, curb T cell function even if PD-1 inhibition is released. Thus, we hypothesize that dual inhibition of PD-1 and DGK–α might be required to fully unleash the T cell's potential in the TME. Current DGK-α inhibitors are not suitable for clinical application. Therefore, we investigated alternative means using an RNA interference (RNAi) approach to target DGK-α alone as well as in combination with PD-1 in T and NK cells. Material and Methods: Knockdown is performed by RNAi using INTASYL TM compounds developed by Phio Pharmaceuticals. INTASYL TM compounds incorporate drug-like properties into the siRNA, resulting in enhanced uptake in the presence of serum with no need for further transfection reagents. Knockdown is analyzed by RT-qPCR and flow cytometry. Functional assays include cytotoxicity, degranulation and cytokine production in tumor mimicking environments. Results: A tumor mimicking in vitro system was developed which allows for the demonstration of functional restoration or prevention of functional loss of cell activity. Using T cell/tumor cell co–cultures at high tumor cell density, functional suppression could be induced in T and NK cells comparable to those observed in the TME. Testing of DGK-α targeting INTASYL TM compounds, silencing of DGK-α was observed in human U2OS osteosarcoma cells. Using a fluorescently labeled compound, highly efficient transfection of human primary immune cells was seen. Combinations of PD-1 and DGK-α targeting compounds are being tested and evaluated for synergism in experimental models. Conclusions: Strong activity of specific T and NK cells is necessary for tumor control. Dual targeting of PD-1 and DGK-α may be required to fully enable T and NK cell reactivity in the TME. Current DGK-α inhibitors do not exhibit the desirable pharmacokinetic/pharmacodynamic (PK/PD) properties for clinical development. The tested self-delivering RNAi technology represents a promising approach to targeting intracellular immune checkpoints such as DGK-α. Reference: Moon EK, Wang L-C, Dolfi DV, Wilson CB, Ranganathan R, Sun J, et al. Multifactorial T-cell hypofunction that is reversible can limit the efficacy of chimeric antigen receptor-transduced human T cells in solid tumors. Clin Cancer Res 2014; 20 (16):4262–73 Disclosure Information: A.S. Herbstritt: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Phio Pharmaceuticals. C. Other Research Support (supplies, equipment, receipt of drugs or other in-kind support); Significant; Phio Pharmaceuticals. P.U. Prinz: None. M. Maxwell: A. Employment (full or part-time); Significant; Phio Pharmaceuticals. M. Kadiyala: A. Employment (full or part-time); Significant; Phio Pharmaceuticals. D. Yan: A. Employment (full or part-time); Significant; Phio Pharmaceuticals. E. Noessner: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Phio Pharmaceuticals. C. Other Research Support (supplies, equipment, receipt of drugs or other in-kind support); Significant; Phio Pharmaceuticals.